Dynamics Characteristic Analysis of Involute Gear with Asymmetric Tooth Considering the Influence of Time-varying Stiffness and Backlash - Qi Chen; Zhigang Yao; Yadong Wang; Yanming Wu (Jixie chuandong)
To obtain more accurate dynamics change law for asymmetric involute gear， dynamics model of asymmetric involute gear is established by introducing time-varying stiffness and gear backlash. The time history chart， phase diagram， Poincaré perception map and FFT spectrogram are obtained by Runge-Kutta method， then the dynamics behaviors of gear with time-varying stiffness and changing backlash are analyzed. The research result shows that the average meshing stiffness of asymmetric involute gears is greater than that of symmetrical involute gears， and the asymmetric involute gear has better dynamics performance. And the one-order harmonic component in the varying mesh stiffness has little effect on dynamics performance， but the average mesh stiffness has greater impact. Moreover， the relationship between the average mesh stiffness and dynamics performance are nonlinear. That is， with the increase of the average meshing stiffness， the dynamics characteristics becomes better from worse， but the average meshing stiffness continues to increase and then the dynamic characteristics become inferior， so the optimal value of the average meshing stiffness should be determined according to the actual working conditions. In addition， when the gear backlash adds， the dynamics performance drops， so as to the symmetrical involute gear. The research here provides a great theoretical significance and practical value for expanding the theoretical system of asymmetric involute gear dynamics and improving its transmission performances.